Upheavals in the Middle East the theory and practice of the revolution - Cohen, Ronen (Lexington Books, 2014)
Upheavals in the Middle East: The Theory and Practice of a Revolution engages with some of the most sensitive issues in the Middle East-revolutions and social protests. The book offers theoretical paradigms that suit the Middle East's conditions-culturally, religiously and historically. It deals with seventeen case studies from a range of Muslim and Arab states and provides a theoretical framework to study other situations all over the world, including cases from the recent Arab Spring. Revolution, as political action, can occur in all societies, but in recent years it has appeared most frequently in the Middle East. Will this trend continue? What makes the Middle Eastern revolution unique and surprising? This book seeks to answer these questions, placing side by side those cases that were successful and those that were doomed to fail.